2020
DOI: 10.1007/s12639-020-01295-5
|View full text |Cite
|
Sign up to set email alerts
|

First record of the nematode, Huffmanela sp. infecting the broomtail wrasse (Cheilinus lunulatus) from Egypt

Abstract: A total of 385 Red Sea coral reef fish representing three species; Broom tail wrasse (Cheilinus lunulatus), Blacktip grouper (Epinephelus fasciatus) and Rabbit fish (Siganus sp.). were examined for the presence of nematode Huffmanela species. The eggs of Huffmanela species were isolated and identified only from the C. lunulatus. The total prevalence of Huffmanela sp. infestation were 69.5%. The highest prevalence was observed in winter and the lowest in spring and summer. The prevalence was increased in correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Previous studies have shown that Huffmanela infection is one of the most common parasitic infections that adversely affect the health of various sh families, worldwide (Moravec & Garibaldi, 2000;Moravec & Garibaldi, 2003;Moravec et al, 2005;Esteves et al, 2009;Moravec & Justine, 2010;Al-Hasson et al, 2019 andEissa et al, 2020). The site of the lesion preference was species dependent, as previously reported for H. lusitana infecting the muscles of pouting Trisopterus luscus (Ramos et al, 2019), while H. paronai was observed in the skin of Xiphias gladius (Justine, 2004).…”
Section: Introductionsupporting
confidence: 56%
“…Previous studies have shown that Huffmanela infection is one of the most common parasitic infections that adversely affect the health of various sh families, worldwide (Moravec & Garibaldi, 2000;Moravec & Garibaldi, 2003;Moravec et al, 2005;Esteves et al, 2009;Moravec & Justine, 2010;Al-Hasson et al, 2019 andEissa et al, 2020). The site of the lesion preference was species dependent, as previously reported for H. lusitana infecting the muscles of pouting Trisopterus luscus (Ramos et al, 2019), while H. paronai was observed in the skin of Xiphias gladius (Justine, 2004).…”
Section: Introductionsupporting
confidence: 56%
“… 62.5–75.3 × 30–36.5 — × 6.3–9.2 3–5.4 Shell surface with protuberance Smooth — × 4.5–6 ND Epinephelus coioides (Serranidae) Muscle Marine Persian Gulf off Jubail (Saudi Arabia) [ 43 ] Huffmanela sp. ND ND ND Smooth NF ND ND Cheilinus lunulatus (Labridae) Swim bladder Marine Red Sea off Hurghada (Egypt) [ 63 ] Huffmanela cf. huffmani 54–66 × 27–33 6–9 × 6–9 3–6 Smooth Transparent UL with minute papillae (spines) ND 3790–12,920 × 21–42 (M); 5810–14,990 × 21–36 (F) Xiphophorus variatus; Gambusia holbrooki (Poeciliidae) Swim bladder, gonad (testis), peritoneum Freshwater West central Florida (USA) [ 5 ] Huffmanela psittacus 46.7–51.7 × 21.7–25 2.30–6.70 × 8.30–10 ND Shell surface with longitudinal, oblique and transverse ridges ND ND 3400–5600 × 18–28 (M); 7500–11,900 × 30–48 (F) Colomesus psittacus (Tetraodontidae) Gills, gill arch, gill mucosa Freshwater (euryhaline fish) Marajó Island, Pará State (Brazil) [ 6 ] Huffmanela selachii …”
Section: Discussionmentioning
confidence: 99%
“…Immunopathological responses induced by intercellular and intracellular infection with eggs or worms of different species of Huffmanela have been previously reported in various fish hosts, reflecting the physical and chemical damage caused by the parasite to the infected tissues. These include granulomatous inflammation (characterized mainly by infiltration of mononuclear phagocytes), inter-cellular edema (spongiosis), cellular adaptive response (hypertrophic, atrophic and hyperplastic changes), degenerative and necrotic changes and degenerative and dystrophic calcification [ 5 , 6 , 10 , 16 , 43 , 59 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Trisopterus luscus Esteves et al (2009) observed in myodegeneration, necrosis, calcification and small granulomas with parasites; fish with hyperinfection showed diffuse histiocytic infiltrate and fibrosis, while fish skin, intestinal serosa and swim bladder showed no abnormalities; Bullard et al (2012) observed intraepithelial inflammation with eosinophilic granulocytes and hyperplasia as well as lymphofollicular hyperplasia in the dermis of Carcharhinus plumbeus. Eissa et al (2021) observed hemorrhagic, necrotic, and chronic inflammatory cell aggregations in the tissue surrounding the swim bladder, as well as tunnels of necrotic tissue that contained the eggs; Attia et al (2021b) observed an intense granulomatous reaction with infiltration of mononuclear inflammatory cells and proliferation of fibrous connective tissue in the histopathology of the muscle fibers of Epinephelus coioides containing the nematodes and eggs. In the histological analysis of the gills of C. psittacus, in this study, numerous eggs were observed between the lamellae, which may have caused hyperplasia of the squamous epithelium of the primary and secondary filaments.…”
Section: Trisopterus Luscus Atlantic Coast Of Portugalmentioning
confidence: 99%